FLASH Irradiation with Proton Beams: Beam Characteristics and Their Implications for Beam Diagnostics - Konrad P. Nesteruk; Serena Psoroulas (Applied Sciences, 2021)
FLASH irradiations use dose-rates orders of magnitude higher than commonly used in patient treatments. Such irradiations have shown interesting normal tissue sparing in cell and animal experiments, and, as such, their potential application to clinical practice is being investigated. Clinical accelerators used in proton therapy facilities can potentially provide FLASH beams; therefore, the topic is of high interest in this field. However, a clear FLASH effect has so far been observed in presence of high dose rates (>40 Gy/s), high delivered dose (tens of Gy), and very short irradiation times (<300 ms). Fulfilling these requirements poses a serious challenge to the beam diagnostics system of clinical facilities. We will review the status and proposed solutions, from the point of view of the beam definitions for FLASH and their implications for beam diagnostics. We will devote particular attention to the topics of beam monitoring and control, as well as absolute dose measurements, since finding viable solutions in these two aspects will be of utmost importance to guarantee that the technique can be adopted quickly and safely in clinical practice.